Tax pressure, farmland management, and agricultural carbon abatement: Empirical evidence from tax-and-fees reform in rural China - Zhang, Xingmin; Wang, Chang’an; Liu, Xiaoqian; Wu, Junqian (Frontiers in Environmental Science, 2022)
Agriculture is the second largest source of carbon emissions in the world. To achieve the strategic goals of “carbon peaking” and “carbon neutrality”, how to effectively control agricultural carbon emissions has become a focus of the Chinese government. As China’s most critical agricultural policy in the early 21st century, assessing the impact of rural tax-and-fees reform (RTFR) on agricultural carbon emissions has vital theoretical and practical implications. Based on panel data of 31 Chinese provinces from 2000 to 2019, this paper constructs a continuous difference-in-differences (CDID) model to identify the effects of RTFR on agricultural carbon emissions, and further tests the mechanisms and heterogeneity of the reform to achieve agricultural carbon emission reduction. The results demonstrate that the reform can effectively reduce the agricultural carbon intensity and improve agricultural carbon efficiency, with the effects of −6.35% and 6.14%, respectively. Moreover, the dynamic effect test shows that the impact of RTFR on agricultural carbon intensity and carbon efficiency is persistent. Furthermore, the mechanism analysis indicates that RTFR achieves the improvement of agricultural operation efficiency and the reduction of agricultural carbon emissions through the expansion of land operation area, the increase of productive investment in agriculture, and the special transfer payment from the central government. However, the impact of RTFR on local government revenue is not conducive to realizing the reform’s carbon reduction effect. The heterogeneity analysis illustrates that the reform policy effects differ in natural climatic conditions, topographical conditions, and crop cultivation structure. The RTFR mostly has a significant negative impact on the carbon emissions generated from material inputs and agricultural production. Therefore, to address the climate change crisis and improve the environmental efficiency of agricultural production, it is necessary to both reduce peasants’ tax burden and implement institutional construction efforts, to further promote the transformation of agricultural production to a low-carbon model.